Therapeutic potential of prenylated stilbenoid macasiamenene F through its anti-inflammatory and cytoprotective effects on LPS-challenged monocytes and microglia. (5th December 2020) - Leláková, Veronika; Béraud-Dufour, Sophie; Hošek, Jan; Šmejkal, Karel; Prachyawarakorn, Vilailak; Pailee, Phanruethai; Widmann, Catherine; Václavík, Jiří; Coppola, Thierry; Mazella, Jean; Blondeau, Nicolas; Heurteaux, Catherine
Abstract: Ethnopharmacological relevance: Macaranga Thou. (Euphorbiaceae) is a large genus that comprises over 300 species distributed between Western Africa and the islands of the South Pacific. Plants of this genus have a long-standing history of use in traditional medicine for different purposes, including the treatment of inflammation. Fresh and dried leaves of certain Macaranga species (e.g. M. tanarius (L.) Müll.Arg.), have been used to treat cuts, bruises, boils, swellings, sores and covering of wounds in general. Several reports described Macaranga spp. being a rich source of polyphenols, such as prenylated stilbenoids and flavonoids, mostly responsible for its biological activity. Similarly, an abundant content of prenylated stilbenes was also described in M. siamensis S.J.Davies, species recently identified (2001) in Thailand. While the respective biological activity of the prenylated stilbenes from M. siamensis was poorly investigated to date, our recent study pointed out the interest as the natural source of several novel anti-inflammatory stilbenoids isolated from this species. Aim of the study: This work investigated the potential anti-inflammatory effects of the stilbenoid macasiamenene F (MF) isolated from M. siamensis S.J.Davies (Euphorbiaceae) on the lipopolysaccharide (LPS)-induced inflammation-like response of monocytes and microglia, major cells involved in the peripheral and central inflammatory response, respectively. Materials and methods: LPS-induced stimulation of TLR4 signaling led to the activation of inflammatory pathways in in vitro models of THP-1 and THP-1-XBlue™-MD2-CD14 human monocytes, BV-2 mouse microglia, and an ex vivo model of brain-sorted mouse microglia. The ability of the stilbenoid MF to intervene in the IкB/NF-кB and MAPKs/AP-1 inflammatory cascade was investigated. The gene and protein expressions of the pro-inflammatory cytokines IL-1β and TNF-α were evaluated at the transcription and translation levels. The protective effect of MF against LPS-triggered microglial loss was assessed by cell counting and the LDH assay. Results: MF demonstrated beneficial effects, reducing both monocyte and microglial inflammation as assessed in vitro . It efficiently inhibited the degradation of IкBα, thereby reducing the NF-кB activity and TNF-α expression in human monocytes. Furthermore, the LPS-induced expression of IL-1β and TNF-α in microglia was dampened by pre-, co-, or post-treatment with MF. In addition to its anti-inflammatory effect, MF demonstrated a cytoprotective effect against the LPS-induced death of BV-2 microglia. Conclusion: Our research into anti-inflammatory and protective effects of MF has shown that it is a promising candidate for further in vitro and in vivo investigations of MF interventions with respect to acute and chronic inflammation, including potentially beneficial effects on the inflammatory component of brain diseases such as stroke and Alzheimer's disease. Graphical abstract: Image 1 Highlights: Stilbenoids from medicinal plants arouse scientific and therapeutic interest for their anti-inflammatory potential. Macasiamenene F (MF) by acting on monocytes reduces systemic inflammation via IκB/NF-κB pathway. MF by acting on LPS-activated microglia reduces pro-inflammatory expression of TNF-α and IL-1β. MF effect is comparable or superior to that of prednisone, a routinely used corticoid anti-inflammatory drug.